Impact of Maternal Education on Breast Feeding and Complementary Feeding Practices of Infants - Safdar, Muhammad Bilal; Naveed, Muhammad; Razzaq, Mujahid; Razaq, Muhammad Umer; Batool, Saima (Journal of University College of Medicine and Dentistry, 2023)
Objectives: To determine the impact of maternal education on incidence of breast feeding, duration and infant complementary feeding practices. Methodology: A Cross sectional study done in Department of Paediatric medicine, University of Lahore Teaching Hospital ,Lahore from October 2020 to March 2021. Non probability consecutive sampling technique, total 198 mothers having child 6 to 12 months were enrolled in study after approval of hospital ethical committee and informed consent from mother. Data was entered and analyzed using SPPS 22. Results: Breast feeding was adopted by 62.8% mothers. Mean duration of breast feeding was 8.52±3.1 months. Regarding initiation of breast feeding 35.1% started immediately after delivery. Regarding introduction of solid feed 27.3% started before 6 months of age. Pre lacteal was given in 35.5% infants. There was no impact of maternal education on frequency of breast feeding, p-value 0.328 but duration of breast-feeding was longer in mother having graduation as compared to mothers having education less than matric i.e. 8.77±2.977 months vs 7.82±3.384 months. Conclusion: Mothers with higher education have greater duration of breast-feeding ad compared to mother with less education.